Algorithm for identifying the location of a potential indoor fire source, its characteristics, and the cause of fire; Process Safety and Environmental Protection; Vol. 208 - Volkov R. S. Roman Sergeevich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Kropotova S. S. Svetlana Sergeevna (2026, 2026)
Title screen